The Shapes of Fancy : Reading for Queer Desire in Early Modern Literature - Varnado, Christine, 1980- (Book collections on Project MUSE., 2020)
"The Shapes of Fancy attempts to move the locus of queerness away from individual bodies or persons to scenes, plots, relations, and networks and, in doing so, redefine queer desire as an affective mode"--